The origins of Anglican moral theology - Sedgwick, P. H. 1948- (Anglican-Episcopal Theology and History, 2018)
In The Origins of Anglican Moral Theology Peter H. Sedgwick shows how Anglican moral theology has a distinctive ethos, drawing on Scripture, Augustine, the medieval theologians (Abelard, Aquinas and Scotus), and the great theologians of the Reformation, such as Luther and Calvin. A series of studies of Tyndale, Perkins, Hooker, Sanderson and Taylor shows the flourishing of this discipline from 1530 to 1670. Anglican moral theology has a coherence which enables it to engage in dialogue with other Christian theological traditions and to present a deeply pastoral but intellectually rigorous theological position. This book is unique because the origins of Anglican moral theology have never been studied in depth before.